KARAKTERISTIK KONSENTRASI CO2 DAN SUHU UDARA AMBIEN DUA TAMAN KOTA DI MALANG - Ninuk Herlina; Wiwin Sumiya D. Yamika; Sandra Yuri Andari (Graduate School Bogor Agricultural University (SPs IPB), 2017)
Malang is a city of education and tourism, where the number of residents in Malang increase every year. It caused the number of motor vehicles increased as well and led to an increase in air temperature and CO2 concentration. City parks play a role in lowering the temperature and CO2 in the vicinity. The purpose of this study was to determine the characteritic CO2 concentration and ambient air temperature in Merdeka Square and Trunojoyo Park Malang City. This research was conducted in February - April 2016 in Merdeka Square and Trunojoyo Park, Malang, East Java. The result of this research showed that the dominant tree in Merdeka Square Park was Beringin (Ficus benjamina), while in Trunojoyo Park was Trembesi (Samanea saman). CO2 concentration at 3 AM in Merdeka quare Park was lower than in Trunojoyo Park that was 478.74 and 481.26 ppm. While CO2 concentration at 1 PM was same in both parks. In Merdeka Square with a tree canopy density of 61.20% had a higher ambient air temperature (32.21oC >30.53oC) at 1PM than in Trunojoyo Park with a tree canopy density of 88.25%. While the ambient air temperature at 3 AM was same in both parks.